INVESTMENT OPPORTUNITIES IN THE UNITED ARAB EMIRATES’ OIL TRADE WITH THE EUROPEAN UNION - Nuvi Nur Syadida; Shelly Maulidina Imelda; Zaky Ismail (CMES (Center of Middle Eastern Studies), 2023)
The United Arab Emirates (UAE) is a country in the Middle East with significant potential for oil reserves. This condition is an advantage that the UAE can leverage to build cooperation with other countries. One potential partner for substantial oil trade investment is the European Union (EU). This research aims to describe the investment opportunities for the UAE in the oil sector with the EU. The method used is descriptive qualitative, involving describing and validating the phenomenon and analyzing it from the perspective of national and international trade interests. The results indicate that, with its oil potential, the UAE has a significant opportunity to invest in oil trade with the EU. This opportunity is enhanced by the UAE's existing positive relationship with the EU. Therefore, the UAE can capitalize on the EU's conditions, which restrict prices and embargo Russian oil, potentially becoming a major oil supplier to the EU. Consequently, the UAE's economy would grow, strengthening its influence in the EU region.